Relative expression of CYP and Arabinogalactan genes in soybean seed coats (Revista Ciência Agronômica, 2023)
The aim of this study was to evaluate the relative expression of two candidate genes, CYP (cyclophilin) andArabinogalactan, possibly involved with seed quality, in contrasting soybean seed coats. The following genotypes wereused: BMX Potência RR and CD 202, both with yellow coats, and TP and IAC, with black coats. The relative expressionof the genes was evaluated by qPCR in seven development phases of the coats of the four genotypes at 25; 30; 35; 40; 45;50 and 55 days after anthesis. The design was completely randomized, with three replicates. The data were submitted toanalysis of variance and the means were compared via the Scott Knott test, at 5% probability. The CYP gene showed greaterexpression in the intermediate stages of development of the coats of the genotypes CD 202 and IAC, yellow coat and blackcoat, respectively. The A rabinogalactan gene presented greater expression in the final stages of coats development of BMXPotência RR.